Presence of Piscirickettsia salmonis in farmed trout (Oncorhynchus mykiss) in Junin, Peru - Yunis A., Jefferson (2015)
This study aimed to determine the possible presence ofPiscirickettsia salmonis in farmed rainbow trout (Oncorhynchus mykiss) in the Mantaro river basin, Junin, Peru, by the indirect inmunofluorescence test (IFAT). Kidney and spleen samples were collected from 180 trout from three fish farms. All samples resulted negative to P. salmonis; however, some individuals showed clinical sings of disease as skin ulcer, melanosis, abdominal swelling and exophthalmoses. Also, in the internal organs was found petechial hemorrhage in liver, pyloric caeca and spleen, splenomegaly and pale liver.